PENGARUH KELOMPOK ACUAN DAN INTERNET MARKETING TERHADAP KEPUTUSAN PEMBELIAN - HARIANTO, AGUS (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract:This study aims to analyze and discussthe influence reference group and internet marketing on purchasing decisions. The study focused on Indosat Mentari Super Internet Smartphone brand SIM Card telecommunication. This research is conclusive. The populations is consumers buy and using card Mentari Super Internet Smartphone in Surabayaaged 15-30 years. The sample inthis study amounted to220??respondentswithsamplingtechniquesjudgmentalsampling. The research instrument used was a questionnaire, documentation and the data obtained were processed using simple regression analysis, followed by analysis of independent samples t test. The results showed that there is significant influence of reference group and internet marketing on purchasing decidions. In this study by looking at the results of the t test, dominant influence internet marketing variable. Keywords:reference group, internet marketing,and purchase decisions.